CSF tau and β-amyloid predict cerebral synucleinopathy in autopsied Lewy body disorders. (20th March 2018) - Irwin, David J.; Xie, Sharon X.; Coughlin, David; Nevler, Naomi; Akhtar, Rizwan S.; McMillan, Corey T.; Lee, Edward B.; Wolk, David A.; Weintraub, Daniel; Chen-Plotkin, Alice; Duda, John E.; Spindler, Meredith; et al.
Abstract : Objective: To test the association of antemortem CSF biomarkers with postmortem pathology in Lewy body disorders (LBD). Methods: Patients with autopsy-confirmed LBD (n = 24) and autopsy-confirmed Alzheimer disease (AD) (n = 23) and cognitively normal (n = 36) controls were studied. In LBD, neuropathologic criteria defined Lewy body α-synuclein (SYN) stages with medium/high AD copathology (SYN + AD = 10) and low/no AD copathology (SYN − AD = 14). Ordinal pathology scores for tau, β-amyloid (Aβ), and SYN pathology were averaged across 7 cortical regions to obtain a global cerebral score for each pathology. CSF total tau (t-tau), phosphorylated tau at threonine181, and Aβ1-42 levels were compared between LBD and control groups and correlated with global cerebral pathology scores in LBD with linear regression. Diagnostic accuracy for postmortem categorization of LBD into SYN + AD vs SYN − AD or neocortical vs brainstem/limbic SYN stage was tested with receiver operating curves. Results: SYN + AD had higher CSF t-tau (mean difference 27.0 ± 8.6 pg/mL) and lower Aβ1-42 (mean difference −84.0 ± 22.9 g/mL) compared to SYN − AD ( p < 0.01, both). Increasing global cerebral tau and plaque scores were associated with higher CSF t-tau ( R 2 = 0.15–0.16, p < 0.05, both) and lower Aβ1-42 ( R 2 = 0.43–0.49, p < 0.001, both), while increasing cerebral SYN scores were associated with lower CSF Aβ1-42 ( R 2 = 0.31, p < 0.001) and higher CSF t-tau/Aβ1-42 ratio ( R 2 = 0.27, p = 0.01). CSF t-tau/Aβ1-42 ratio had 100% specificity and 90% sensitivity for SYN + AD, and CSF Aβ1-42 had 77% specificity and 82% sensitivity for neocortical SYN stage. Conclusions: Higher antemortem CSF t-tau/Aβ1-42 and lower Aβ1-42 levels are predictive of increasing cerebral AD and SYN pathology. These biomarkers may identify patients with LBD vulnerable to cortical SYN pathology who may benefit from both SYN and AD-targeted disease-modifying therapies.